ANALISIS HUBUNGAN TINGKAT KONSUMSI ENERGI DAN PROTEIN TERHADAP STATUS GIZI PADA ANAK USIA 2-5 TAHUN - Elfina Yulidar; Santi Aprilian Lestaluhu; Vina Anggraini; Octovina Soumokil (Ensiklopedia of Journal, 2026)
Abstract: Malnutrition is one of the nutritional problems in toddlers, characterized by thinness. One important factor that influences malnutrition is food consumption, both in terms of quantity and quality. The purpose of this study was to analyze the relationship between energy and protein consumption levels and nutritional status in children aged 2-5 years. A cross-sectional study design was used in this study. The study was conducted in the working area of the Srandakan Community Health Center. The study was conducted in April 2025. The study population consisted of mothers who had toddlers in the working area of the Srandakan Community Health Center. The sample consisted of 65 respondents. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate analysis. The results of this study indicate a relationship between energy consumption levels (p value: 0.000) and protein consumption levels (p value: 0.003) with the nutritional status of toddlers. It is recommended that parents with toddlers pay attention to the food consumed by their toddlers and increase their consumption by providing additional food.Keywords: Toddlers, Energy, Protein.